Transition Bimetal Based MOF Nanosheets for Robust Aqueous Zn Battery - Wan, Jun; Li, Junfeng; Xiao, Zhiheng; Tang, Dandan; Wang, Bo; Xiao, Yongjun; Xu, Weilin (Frontiers in Materials, 2020)
High-performance, good stability, low-cost and environmentally friendly batteries are important for portable electronics and electric vehicles. Compared with the high-energy density lithium-ion batteries, aqueous rechargeable battery has been extensively researched due to high safety, low cost and much better rate performance. Here, we report a one-step approach to fabricate porous Ni-Cu metal–organic framework (MOF) nanosheet arrays structures for stable energy storage with a high-energy (71.2 mWh cm−3) and high-stability (capacity retention of ≈91% after 2500 cycles) performance. Furthermore, we synthesized various porous homogeneous Ni-Co, Ni-Zn, Ni-Fe and Ni-Mn bimetal MOF structures with high surface area and conductivity utilizing this rational design. This work provides a simple efficient strategy for constructing porous homogeneous bimetal MOF nanosheet arrays with high energy and stability performance, holding a great potential for future multifunctional electronic devices.